A multi-scale process for mechanical characterization of ceramic materials produced by Direct Ink Writing - Raphael Thiraux; Alexander D. Dupuy; Kate M. Ainger; Lorenzo Valdevit (Open Ceramics, 2024)
Mechanical characterization of ceramics is challenging, as the statistical nature of their strength requires numerous specimens to extract reliable distribution parameters. Here, we first propose a high-throughput testing procedure that allows extraction of statistical information on the strength of ceramic materials. We process large numbers of bending specimens from low volumes of material via Direct Ink Writing (DIW), and rapidly characterize them to extract Weibull parameters for bending strength. After investigating five ceramics and downselecting two formulations, we develop a multi-scale procedure to explore the impact of printing-induced defects on the strength distribution of DIW-processed ceramics. Finally, we demonstrate that a judicious choice of the printing strategy produces porous architected structures which can significantly exceed the strength of fully dense DIW-produced monolithic materials. While the results are presented on DIW-processed alumina-based ceramics, the approach is versatile and can provide rapid statistical data on the strength of many ceramic materials.